Hominins likely occupied northern Europe before one million years ago. Issue 1 (16th November 2022) - Key, Alastair; Ashton, Nick
Abstract: Our understanding of when hominins first reached northern Europe is dependent on a fragmented archaeological and fossil record known from as early as marine isotope stage (MIS) 21 or 25 (c. 840 or 950 thousand years ago [Ka]). This contrasts sharply with southern Europe, where hominin occupation is evidenced from MIS 37 to 45 (c. 1.22 or 1.39 million years ago [Ma]). Northern Europe, however, exhibits climatic, geological, demographic, and historical disadvantages when it comes to preserving fossil and archaeological evidence of early hominin habitation. It is argued here that perceived differences in first occupation timings between the two European regions needs to be revised in light of these factors. To enhance this understanding, optimal linear estimation models are run using data from the current fossil and artefact record. Results suggest northern Europe to have first been occupied as early as 1.16 Ma, or as late as 913 Ka. These timings could represent minimum date expectations and be extended through future archaeological and fossil discoveries.